KEDISIPLINAN DAN MOTIVASI DALAM UPAYA MENINGKATKAN PRESTASI KERJA KARYAWAN PADA PT SIMED PRAKARSA - Roosna anam (Ecobuss, 2019)
The purpose of this study is to find out and help in improving employee performance at PT. Simed Indonesianinitiative. The subjects in this study were 15 employees of PT Simed Prakarsa Indonesia. This study uses adescriptive research approach using a qualitative approach. The results in this study are seen in Table 2. Theresults of the variables with advanced stages. Several categories at PT Simed Prakarsa Indonesia are at a highlevel. But this will not affect the discipline of employees who have a value of 4. Encouragement or motivation byemployees to give the best to the company. Work performance that is used by employees in a certain period of time,which company works Usually in the form of numbers or certain symbols. Then with these numbers or symbols,other people or employees themselves will be able to find out about the work performance that has been achieved.Based on the answers to the informants who used the information related to them and were very effective.Keywords: Discipline, Motivation, Work Achievement